Lock-in Thermography Basics and Use for Evaluating Electronic Devices and Materials - Breitenstein, Otwin (Springer Series in Advanced Microelectronics,, 2018)
This book discusses lock-in thermography (LIT) as a dynamic variant of the widely known IR thermography. It focuses on applications to electronic devices and materials, but also includes chapters addressing non-destructive evaluation. Periodically modulating heat sources allows a much-improved signal-to-noise ratio (up to 1000x) and a far better lateral resolution compared to steady-state thermography. Reviewing various experimental approaches to LIT, particularly the commercial LIT systems available, this 3rd edition introduces new LIT applications, such as illuminated LIT applied to solar cells, non-thermal LIT lifetime mapping and LIT application to spin caloritronics problems. Numerous LIT investigation case studies are also included.